Penggunaan Strategi Snowball Throwing dalam Meningkatkan Konsentrasi Belajar PKn Siswa Kelas V SD Muhammadiyah 21 Baluwarti Surakarta Tahun 2015/2016 - Kanastiowati, Novi; , Dra. Sri Hartini, S.H., M.Pd (2016)
This research is a classroom action research conducted in two cycles. The purpose to increase the concentration of civics education through a strategy of snowball throwing class V students of SD Muhammadiyah Surakarta Baluwarti 21. Each cycle consisted of one meeting, each cycle through four stages: planning, implementation, observation, and reflection. The recipients subject action is all fifth grade students of SD Muhammadiyah 21 Baluwarti Surakarta , amounting to 18 students as, subject of the perpetrator is researcher and teacher. Data collection techniques by using the method of observation, interviews, and documentation. Data analysis techniques used in this study is an interactive model that includes: data presentation,data reduction,and conclusion or verification.The results showed an increase in the concentrations studied civics students after a class action was held using the snowball throwing. It can be seen from the following indicators: Pay attention to any subject matter presented by the teacher to increase, this is 39% in pre-cycle, 50% in the first cycle, and 89% in the second cycle. Can respond and understand any given subject matter, this is 39% in pre-cycle, 55.50% in the first cycle, and 77% in the second cycle. Always be active by asking questions and arguing about the subject matter presented by the teacher,this is 22% in pre-cycle, 50% in the first cycle, and 77% in the second cycle. Answered properly and correctly every question the teacher, this is 22% in pre-cycle, 55.50% in the first cycle, and 83% in the second cycle. Therefore, it can be seen that through the use of throwing snowball strategy may increase the concentrations studied civics class V students of SD Muhammadiyah Surakarta 21 Baluwarti year 2015/2016.